Representasi Isu Kesehatan Mental dalam Desain Cover Album Mantra Mantra Kunto Aji - Avisenna, Muhammad Ibnu; Marwan, Rudi Heri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Mental health issues in Indonesian society are among the most prevalent, and through the Mantra Mantra album, Kunto Aji explicitly highlights the importance of mental well-being, both through its lyrics and its visual representation. This study employs a qualitative method with Roland Barthes’ semiotic approach, analyzing visual signs at the levels of denotation, connotation, and myth. The findings indicate that the visual elements presented in the Mantra Mantra album cover carry symbolic meanings closely related to the concepts of stress release, self-reflection, and the normalization of mental health discourse within society.